Peran Manajemen Kinerja Untuk Meningkatkan Mutu Pendidikan Di Sekolah - Aswaruddin Aswaruddin; Fazli Abdillah; Ezra Aisaura; Sri Rahayu Ningsih; Casyariadi Vana Hafidza; Adilla Aisyahrani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to explore the role of performance management in improving the quality of education in schools. Quality education is an important aspect in achieving quality education goals, and performance management is considered an effective tool to achieve this. This research method involves literature study, secondary data analysis, and interviews with educational professionals. The research results show that performance management has a key role in improving the quality of education, through measuring, monitoring and improving the performance of teachers, students and educational staff. Implementing performance management in education can also increase school accountability, transparency and more effective decision making. In the era of digital education, information technology and performance management information systems can become valuable tools in managing data, evaluating and reporting educational performance. In conclusion, performance management has a very important role in improving the quality of education in schools. By implementing appropriate performance management strategies and practices, schools can optimize teacher and student performance, achieve better educational goals, and contribute to improving the overall quality of education.